Anai Ube' Ta: Makna Tembakau Dalam Kehidupan Masyarakat di Siberut Selatan, Kepulauan Mentawai - Ade Irwandi (Balale' : Jurnal Antropologi, 2021)
This study describes the knowledge of the Mentawai people about plants used as cigarettes. These plants include koraraiba, bulug gettek, paddoka, kaokok, ube' leleu and the panorama they roll with banana leaves (bulug magok sareu and Bulug magok soggunei). Processed from each of these plants they call ube'. The word ube' for the Mentawai people means cigarettes and tobacco. Ube' is used in the socio-cultural atmosphere of the Mentawai people such as rituals (punen), hunting, gathering (silaturahmi) and interacting with outsiders (sasareu).In a ritual led by a sikerei usually uses ube' as an intermediary (gaud) for worship, conditions for requesting permission, thanks and as gifts. Because at the time of the sikerei ceremony, the ancestral spirit (the spirit of the ruler) is called to assist in the ritual, so the ube' is offered in the ceremony and besides that it is also smoked together. Ube' is also a requirement and as an application for permission to the forest authorities (taikaleleu) when entering the forest for hunting purposes or opening new fields. In the Mentawai community, ube' is also used to establish human relations and create an atmosphere of intimacy, togetherness and strengthen inter-tribal relations (uma). So often heard the word anai ube' ta which means double, between asking and offering ube' to someone.